An Empirical Study on the Impact of Supply Chain Finance on the Performance of the Automobile Industry in the Post-COVID-19 Era - Li, Xiaowen; Chen, Jun (Recent Patents on Engineering, 2025)
BackgroundIn recent years, trade on credit has become increasingly common around the world, exposing companies in the supply chain to significantly increased financial risk due to extended billing periods. As an innovative financing model, supply chain finance (SCF) has received a lot of attention.ObjectiveThe goal of this work is to examine the impact of supply chain finance on the performance of the automobile industry in the post-COVID-19 era.MethodsAfter an in-depth understanding of the relevant theoretical literature, two models of inquiry are established in this patent paper, and the relevant data are collected from the CSMAR database for a sample of some enterprises in the automotive industry in the listed market, followed by an empirical analysis using the Stata 16.0. Then, the fixed effects model (FEM) and difference-in-difference model (DID) are used to test the hypothesis.ResultsThe results show a significant impact of supply chain finance on the performance of automobile firms. It is effective in improving the flow of funds and contributes to the performance of enterprises in the automotive industry. Besides, we have registered a software patent named “Cross-border e-commerce big data supply chain information management system” to aid our study.ConclusionIn the context of the pandemic, supply chain finance can effectively help enterprises reduce the risk of bankruptcy due to capital rupture and provide a guarantee for the sustainable development of automobile industry enterprises.
Keywords: DID model